1996
DOI: 10.1016/s0960-9822(02)00510-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated apoptosis in a plant hypersensitive disease resistance response

Abstract: These observations establish a signal function for Ca2+ downstream of the oxidative burst in the activation of a physiological cell death program in soybean cells that is similar to apoptosis in animals. That the characteristic cell corpse morphology is also induced in Arabidopsis and tobacco by different avirulence signals suggests that apoptosis may prove to be a common, but not necessarily ubiquitous, feature of incompatible plant-pathogen interactions. Emerging similarities between facets of hypersensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
401
5
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(428 citation statements)
references
References 47 publications
(72 reference statements)
17
401
5
5
Order By: Relevance
“…Included are self-incompatibility of pollen, aleurone differentiation, aerenchyma formation, HR and leaf senescence. [51][52][53][54] Additional data confirm a role of CaMBP or channel in pathogen defense. The Arabidopsis Dnd1 gene, that encodes a cyclic nucleotidedependent calcium channel, is required for the activation of HR-induced cell death.…”
Section: Discussionmentioning
confidence: 82%
“…Included are self-incompatibility of pollen, aleurone differentiation, aerenchyma formation, HR and leaf senescence. [51][52][53][54] Additional data confirm a role of CaMBP or channel in pathogen defense. The Arabidopsis Dnd1 gene, that encodes a cyclic nucleotidedependent calcium channel, is required for the activation of HR-induced cell death.…”
Section: Discussionmentioning
confidence: 82%
“…In several species of cyanobacteria and unicellular algae, the production of H 2 O 2 can coordinate a series of cellular responses including the induction of programmed cell death or apoptosis (Korsmeyer et al, 1995;Levine et al, 1996;Vardi et al, 1999). For example, ultraviolet radiation (particularly UV-B: 280-320 nm) has a detrimental effect on the development and general metabolism of cyanobacteria (Tyagi et al, 1992;Hader, 1998, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several groups have reported that extracellular EGTA can inhibit the mobilization of selected disease resistance mechanisms (52,53). Other workers have shown that introduction of exogenous Ca 2ϩ into resting cells can initiate a defense response in the absence of the usually required elicitors (16,54). Still other laboratories have demonstrated that Ca 2ϩ channel blockers such as La 3ϩ can prevent expression of a normal pathogen resistance mechanism when conditions are otherwise designed to stimulate its induction (52,54).…”
Section: Fig 2 Effect Of Plant Defense Elicitors On Intracellular Cmentioning
confidence: 99%
“…Other workers have shown that introduction of exogenous Ca 2ϩ into resting cells can initiate a defense response in the absence of the usually required elicitors (16,54). Still other laboratories have demonstrated that Ca 2ϩ channel blockers such as La 3ϩ can prevent expression of a normal pathogen resistance mechanism when conditions are otherwise designed to stimulate its induction (52,54). Nevertheless, it has never been determined wherein Ca 2ϩ actually exerts control over processes leading to disease resistance.…”
Section: Fig 2 Effect Of Plant Defense Elicitors On Intracellular Cmentioning
confidence: 99%